The distribution of the ABO and rhesus blood groups among diabetes mellitus patients in Zintan City, Libya - Abubakeer, Adell; Salem, Retaj Ali Salem; Ali, Amira Mohammed Ali; Mohammed, Amani Altaher Mohammed (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2024)
Numerous studies have explored the potential connection between ABO blood groups and the risk of developing specific illnesses in the literature. This study aimed to examine the distribution of ABO blood and rhesus (Rh) groups among patients with diabetes mellitus (DM) at the Endocrinology and Diabetes Center in Al-Zintan City, Libya. This cross-sectional study took place from October to December 2022, involving 144 blood samples (99 from diabetic patients and 45 from non-diabetic individuals aged 15 to 85 years). Ethical approval and informed consent were obtained from the Endocrinology and Diabetes Center in Al-Zintan, where all laboratory work and statistical analysis using SPSS were conducted. Of the diabetic patients, 46% were male and 53% were female. The test results showed no association between ABO and Rh blood groups in individuals with diabetes mellitus. Among diabetics, the O blood group was most prevalent at 49%, followed by A (34%), B (11%), and AB (5%). Rh+ was more common (n=88) than Rh- (n=11), with no significant difference (p=0.733). Gender distribution also showed no significant difference (p>0.05). The O blood group was more common in females (55.10%) than males (44.90%), and the B blood group was found more often in females (72.73%) than in males (27.27%). This research shows no significant relationship between ABO and Rh blood types and diabetes mellitus occurrence among patients at the endocrinology and diabetes center in Al-Zintan City. Blood group variations do not influence diabetes prevalence or characteristics in this population.